The Relationship between Noise Intensity and Blood Pressure in Communities Around Bangkal Village - Akbar, Muhammad Shaufi; Junaidi, Junaidi; Ali As, Zulfikar; Khair, Abdul (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Noise is a serious problem because it can have an impact on health, one of which is high blood pressure (hypertension). Noise can come from inside or outside the house. One source of noise from outside the house is traffic. Noise comes from the sound produced by motorized vehicles, especially from the engine, exhaust, and the interaction between the wheels and the road. This research aims to determine and analyze the relationship between noise intensity and blood pressure in the community around Bangkal Village. This research is observational analytic, using a cross-sectional design. Observations were made on 68 people, consisting of 40 people for the cluster on the side of the road and 28 people for the cluster 32 m from the road. Data were analyzed using the gamma correlation test. A sound level meter was used to collect noise data, a blood pressure meter was used to collect blood pressure data, and a questionnaire was used to collect respondent characteristics. The research results show that noise ranges between 46.6 dBA – 72.3 dBA. Twelve people (40%) suffered from high blood pressure, and 28 people (60%) had normal blood pressure. There is no significant relationship between noise intensity and blood pressure. This information is helpful for future researchers conducting further research by considering other variables or carrying out noise measurements in the house (indoors).